The influence of fixation on the cardiac tissue in a 1‐year observation of swine hearts. (30th July 2018) - Hołda, Mateusz K.; Hołda, Jakub; Koziej, Mateusz; Tyrak, Kamil; Klimek‐Piotrowska, Wiesława
Abstract: Aim: The aim of this study was to investigate the influence of formaldehyde‐based fixation on dimension, weight and shape of cardiac tissue during a 1‐year observation. Materials and methods: Seven measuring sites were permanently marked in 40 swine hearts prior to fixation. Four study groups ( n  = 10 each) were assembled that differed only in concentration and the type of fixative. The fixatives were 2%, 4% or 10% formaldehyde phosphate‐buffered solution (FPBS) and alcoholic formalin. The samples were measured before fixation and then after fixation at 1 week, 3, 6 and 12 months. Results: At the 3‐month point, the 10% FPBS had caused significant changes in the smallest number of parameters, while the 2% FPBS affected the greatest number of dimensions. The most significant changes included chordae tendineae shrinkage and an increase in muscle thickness. After 6 months, the most significant changes were observed in 2% and 4% FPBSs and were also mainly associated with an increase in muscle thickness and chordae tendineae shrinkage. 1‐year preservation compared to the baseline showed the most significant changes in muscle tissue thickness and hearth weight. The artery diameter decreased in long‐term fixation in every tested solution. For atrial and angle measurements, 4% FPBS caused most significant changes among investigated fixatives. Conclusions: In all tested solutions, long‐term fixation significantly changed cardiac tissue dimension compared to the nonpreserved samples. Short‐term to 1‐year fixation changes are smaller, but they should not be neglected. Different fixatives should be used depending on the character of the planned measurements.